2009
DOI: 10.1152/jn.91099.2008
|View full text |Cite
|
Sign up to set email alerts
|

Area Spt in the Human Planum Temporale Supports Sensory-Motor Integration for Speech Processing

Abstract: Processing incoming sensory information and transforming this input into appropriate motor responses is a critical and ongoing aspect of our moment-to-moment interaction with the environment. While the neural mechanisms in the posterior parietal cortex (PPC) that support the transformation of sensory inputs into simple eye or limb movements has received a great deal of empirical attention-in part because these processes are easy to study in nonhuman primates-little work has been done on sensory-motor transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
211
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(232 citation statements)
references
References 47 publications
16
211
2
Order By: Relevance
“…Macroscopically, area PT has been described as a computational hub, which segregates spectrotemporal patterns, compares them to stored patterns, and outputs auditory objects (Griffiths and Warren, 2002), which is compatible with our results. Location and functional role of a smaller part of our clusters in PT is accordant with Spt, a functional subdivision of PT, which has been described as a sensory-motor integration region for the vocal tract motor effector (Hickok and Poeppel, 2007;Hickok et al, 2009). This is in line with the suggestion that PT is part of the dorsal stream of auditory processing (revised to include language in addition to spatial functions) and possesses the representation of templates for doable articulations, effectively disambiguating phonological information (Rauschecker and Scott, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Macroscopically, area PT has been described as a computational hub, which segregates spectrotemporal patterns, compares them to stored patterns, and outputs auditory objects (Griffiths and Warren, 2002), which is compatible with our results. Location and functional role of a smaller part of our clusters in PT is accordant with Spt, a functional subdivision of PT, which has been described as a sensory-motor integration region for the vocal tract motor effector (Hickok and Poeppel, 2007;Hickok et al, 2009). This is in line with the suggestion that PT is part of the dorsal stream of auditory processing (revised to include language in addition to spatial functions) and possesses the representation of templates for doable articulations, effectively disambiguating phonological information (Rauschecker and Scott, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Left hemispheric motor speech areas have been found to be involved both in the subvocal rehearsal and perception of the syllables /ba/ and /da/ (Pulvermüller et al, 2006) and of spoken words (Schomers et al, 2014). Furthermore, speech motor regions may bias the perception of ambiguous speech syllables under noisy conditions (D'Ausilio et al, 2009;Du et al, 2014) and have been suggested to be specifically important for the performance of tasks requiring subvocal rehearsal (Hickok and Poeppel, 2007;Krieger-Redwood et al, 2013). However, the involvement of (pre)motor cortex in speech perception may also reflect an epiphenomenal consequence of interconnected networks for speech perception and production .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the anterior SMG was found to generalize manner of articulation in the right hemisphere and place of articulation in the left (10 mm searchlight radius) and right (20 mm searchlight radius) hemisphere. Nearby regions involving the inferior parietal lobe (Raizada and Poldrack, 2007;Moser et al, 2009;Kilian-Hü tten et al, 2011) and sylvian-parietaltemporal regions (Caplan and Waters, 1995;Hickok et al, 2003Hickok et al, , 2009Buchsbaum et al, 2011) have been implicated in sensorimotor integration during speech perception as well as in mapping auditory targets of speech sounds before the initiation of speech production Guenther and Vladusich, 2012). Here, we show the sensitivity of SMG to represent articulatory features of spoken syllables during speech perception in the absence of an explicit and active task, such as repetition (Caplan and Waters, 1995;Hickok et al, 2009) or music humming (Hickok et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations